Definition of clinical immunology around the globe - José C. Crispín; José C. Crispín; José C. Crispín; Tineke Cantaert; Tineke Cantaert; Alberto Pinzon-Charry; Alberto Pinzon-Charry; Alberto Pinzon-Charry; Domenico Mavilio; Domenico Mavilio; Domenico Mavilio; Ahmed Seri; et al. (Frontiers in Immunology)
Immunology has gradually become a core part of many medical specialties. Immune cells and immune mediators are now known to participate in the pathogenesis of a wide variety of diseases and therapies based on the modulation of immune function are increasingly used. Traditionally, clinical immunologists have studied patients with inborn errors of immunity (IEI), previously known as primary immunodeficiencies, and with allergic conditions. More recently, clinical immunology has become involved with a broader array of disorders. The Clinical Immunology Committee of the International Union of Immunological Societies set out to understand how clinical immunologists perceive their specialty to identify similarities and differences in training and practice around the globe. For this purpose, a specific questionnaire was designed and distributed amongst our member societies. More than 500 participants answered the questionnaire, 80% of whom had completed their training. Roughly two thirds of respondents were physicians directly involved in patient care. We found that though the number of diseases and processes in which immune mechanisms are involved has considerably grown, 90% of participants agree with the 1993 World Health Organization definition of Clinical Immunology. We propose that the increased complexity of the field opens a need for multidisciplinary teams of clinicians and basic researchers and for a broader training of specialists.